Inflammatory proteins related to depression in multiple sclerosis: A systematic review and meta-analysis - L.A. Kiropoulos; V. Rozenblat; N. Baes (Brain, Behavior, & Immunity - Health)
Background: Up to 50% of individuals with multiple sclerosis (MS) experience depression. Depression has been accompanied by increases in inflammatory proteins. This meta-analysis summarized the data on inflammatory protein concentrations and level of depression in individuals with MS. Methods: We performed a meta-analysis of studies measuring inflammatory protein concentrations and level of depression in individuals with MS with a database search of the English literature (to October 2024) and a manual search of references. Quality of evidence was also assessed. Results: Fifteen studies involving measurements of inflammatory proteins and level of depression in 1102 individuals with MS were included in the meta-analysis: five for interleukin (IL)-10 (LPS and PHA), four for tumour necrosis factor (TNF)-α, four for interferon (IFN)-γ, and four for IL-6 (LPS and PHA). A meta-analysis showed that higher concentrations of TNF-α, IFN-γ, IL-6 and IL-10 were significantly associated with higher levels of depression in individuals with MS (r = 0.35, 95% CI [0.6,0.03], p = .015. Meta-analyses undertaken for individual inflammatory proteins of IFN-γ and IL-10 found positive associations between these proteins and level of depression although these did not reach statistical significance. Most studies were rated ‘poor quality’. Conclusion: This meta-analysis reports significant associations between higher concentrations of TNF-α, IFN-γ, IL-6 and IL-10 and level of depresson in individuals with MS. Future longitudinal studies with improved reporting of data are needed to replicate these results and confirm the mechanisms through which these inflammatory proteins are present. Meta-analytic findings lend support to depression being associated with the activation of the inflammatory system in individuals with MS.